IMPLEMENTATION OF HIGH SPEED DATA COMMUNICATION BASED ON MESH NETWORK ON ROUTER TL-MR3020 - Tirta Kelana, Raymond
Indonesia, as a developing country, needs equality in network and infrastructure. In remote areas, these two things are not sufficient due to the high-cost need to build the proper communication network. To solve this issue, a design communication network was made to produce a communication device that could transmit sound and images. This device uses B.A.T.M.A.N. protocol with a router which the operation system (OS) was changed into OpenWRT. This protocol is used because of its characteristics which can integrate between devices easily, not require an IP, and able to optimize data network rate. Communication using the B.A.T.M.A.N. protocol can be done easily and independently with an appropriate wireless configuration. OpenWRT is chosen as the OS because of its stability, ability to reduce latency/lag, can operate in long duration, high security, and free installation. This research would start by simulation using the Mininet-Wifi to see the characteristics of the B.A.T.M.A.N. protocol and continue with the live experiment using a router with an OpenWRT OS, and other packages installed. In this research, there would be a VoIP server tested using B.A.T.M.A.N. protocol where its characteristics would be studied so that it could be further developed into a prototype that could transfer image and sound. The conclusion of this research is that VoIP call maximum hop is 6, and video call maximum hop is 5.